ANTIFUNGUS EFFECTIVENESS OF CITRUS AMBLYCARPA PEEL, CITRUS HYSTRIX DC PEEL AND CITRUS AURANTIFOLIA PEEL EXTRACT (Against the Growth of Candida albicans) - Resha Yusnida; Debby Saputera; Sherli Diana; Fajar Kusuma Dwi Kurniawan; Maharani Laillyza Apriasari (FKG ULM, 2025)
Background: Candida albicans is a microorganism that causes many infections in the oral cavity. To treat infections caused by Candida albicans, antifungal therapy is needed. Alternative treatments for fungal infections can utilize traditional medicines, namely by using citrus amblycarpa peel extract, citrus hystrix DC peel, and citrus aurantifolia peel because they contain alkaloids, flavonoids, saponins, and tannins. Objective: Analyzing the antifungal effects of 100% concentration of citrus amblycarpa peel extract, 100% concentration of citrus hystrix DC peel, and 100% concentration of citrus aurantifolia peel on the growth of Candida albicans. Method: This study was a true experimental laboratory study with a post test only control group design, consisting of four treatment groups. Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MKC). Result: Parametric analysis using One Way Anova and Post Hoc Bonferroni KHM showed that there were significant differences in each treatment group and Post Hoc Games Howell test analysis showed that citrus amblycarpa peel extract showed no significant difference to citrus hystrik DC peel, citrus aurantifolia peel extract 100% concentration, while the aquades as a negative control there is a significant difference. Conclusion: Citrus amblycarpa peel extract, citrus hystrix DC peel extract, citrus aurantifolia peel 100% concentration, and aquades as a negative control had inhibitory effect on Candida albicans. Citrus amblycarpa peel extract concentration of 100% has killing power.